KINERJA SEKDES PNS DI KECAMATAN SAWIT KABUPATEN BOYOLALI (KAJIAN DI DESA CEPOKOSAWIT DAN DESA GOMBANG - Sri Purnama Sari; Yuwanto .; Rina Martini (Journal of Politic and Government Studies, 2015)
The implementation of the village administration takes the role of villageofficials, as well as the secretary of the village in the Sawit district of Boyolali is areliable, professionalism and competent in their fields of a village secretary.Theappointment of the secretary of the village was being expected to motivate othervillage officials, who is not being civil servants to be more active, whilethe secretaryof the village carry out their duties and functions. Therefore, the formulation of theproblem in this research is